Social media and strategic communications - Noor Al-Deen, Hana S., 1951-; Hendricks, John Allen, 1970- (Palgrave Macmillan, 2013)
"Social Media and Strategic Communications provides comprehensive and original scholarly research that exhibits the strategic implementation of social media in both advertising and public relations. Policies, codes of ethics, and recommendations set by business organizations for best practices are also examined. Various research methodologies are employed to analyze the communication strategies applied by advertisers and public relations practitioners who have embraced social media as an integral part of their operations in order to develop and maintain strong and lasting relationships with customers and the public"-- Resumé vydavatele
Keywords: sociální média; reklamní strategie; internetový marketing; internetová reklama; mediální komunikace; public relations; social media; advertising strategy; Internet marketing; Internet advertising; communication in mass media; sborníky; papers of several authors